Rights and obligations of the patients in the primary health care - Marzec, Alicja; Pluta, Agnieszka; Faleńczyk, Kamila; Budnik-Szymoniuk, Maria; Lewicka, Marta (Journal of Education, Health and Sport, 2019)
The rights patient as a set of rights due to the use of health services in Poland result from the Constitution of the Republic of Poland. They are regulated by the whole regulations. The aim of this work is to present the rights patient and duties in primary care.